Isolation and Characterization of Microsatellite Markers for Hypochaeris incana (Asteraceae) and Close Relatives - Wang, Ping (2017)
Premise of the study: We developed microsatellite markers to study clonal growth and interspecific hybridization in the Patagonian and subantarctic plant Hypochaeris incana (Asteraceae) and its closest relatives. Methods and Results: We developed primers for microsatellite loci from 454 sequence reads of genomic DNA of H. incana. We tested them on individuals of H. acaulis, H. hookeri, H. incana, H. palustris, and H. tenuifolia. We selected 15 polymorphic microsatellite loci, which delivered clearly scorable fragments in most or all species. With mean values between 0.7 and 0.8, the expected heterozygosity in populations of H. incana is high. Conclusions: Due to high levels of polymorphism, the developed markers make it possible to distinguish between genets and ramets in H. incana. In some markers, null alleles complicate the scoring of genotypes in tetraploids. All of the developed markers are suitable to study interspecific hybridization among this group of closely related species.